Managing university innovation as a contribution to local development - Castro Villa, Wilfredo Manuel; García Mera, Silvia Magdalena; Arteaga Linzan, Monica Maria; Tituano Zambrano, Mariana del Jesús (Revista Venezolana de Gerencia, 2026)
Universities face significant challenges in contributing to local development, needing a transformation of existing mechanisms and procedures. This shift requires more than incremental improvements; it demands structural innovations in traditional internal dynamics. This article proposes a theoretical and methodological framework designed to support university innovation management as a catalyst for local development. This framework is operationalized through a namesake model. Quantitative and qualitative methods and techniques were employed in the development of the research. Key methodological tools included documentary reviews, checklists, and interviews with internal and external stakeholders, as well as a cross-impact matrix. The application of these tools revealed the integrative and strategic nature of the core category and its alignment with the university’s substantive processes. The theoretical foundations established here address the gaps identified in previous research. Furthermore, the model—structured around four core transformation elements—offers a pertinent alternative for universities, highlighting the importance of innovation management in fulfilling their social mission.